PEMANFAATAN AIR CUCIAN BERAS SEBAGAI PUPUK ORGANIK CAIR (JAKABA) UNTUK PERTANIAN BERKELANJUTAN DI DESA MONTONG BETER, SAKRA BARAT, LOMBOK TIMUR. - nursaida, Imanda; baihaqi, Yusran; Mardiana, Jaeni; Amalia Wardani, Putri; Nugroho Manan, Hatta; Intang Masgustipati, Routh; Sajendra, Riwa; Jumratul Husnah, Nur; Mu'azarah, Durriyul; Safitri, Maulani (Jurnal Wicara, 2025)
In an effort to support sustainable organic farming in Montong Beter Village, West Sakra District, East Lombok Regency, Mataram University KKN-PMD students use rice washing water as liquid organic plant fertilizer. The agricultural sector is one of the important aspects in the sustainability of people's lives, especially in Montong Beter Village, West Sakra District, East Lombok Regency at this time, most people rely on agricultural products as a foundation for life in the village's economic sector. However, in the midst of agricultural land degradation due to the large amount of residues from chemicals that have a significant impact on the environment, therefore environmentally friendly technology-based innovations are needed as a solution to balance on agricultural land and can optimize the productivity of sustainable agricultural products. Therefore, a concrete solution to overcome this dilemma is to utilize rice washing water from household waste as liquid organic fertilizer (JAKABA). The program and ideas offered aim to introduce and implement the invention of JAKABA to optimize agricultural products that are of higher quality and free from chemicals. The methods used in this program are socialization, training in making liquid organic fertilizer, and assistance in implementing the use of JAKABA on community land. The results of this activity show an effective solution in improving the quality of soil fertility and can provide higher quality agricultural products and have an impact on Ecosystem Balance.